New perspectives for disability studies: a Portuguese case (Cadernos de Sociomuseologia, 2024)
This text draws on aspects of the everyday life of the Portuguese poet and accessibility consultant Paulo Reis Simões to discuss how societies in general (do not) include people with disabilities. It begins by presenting the main models for understanding disability issues, providing context and outlining the most significant historical events that shaped them. Using the framework of Science, Technology, and Society (STS) studies, the concepts of agency, collective, composition, and translation are introduced as contributions to disability studies, whose main models are briefly presented in the first section. Adopting a narrative style typical of Science, Technology, and Society studies, these referenced concepts emerge from Paulo’s own narrative, giving an empirical character to this work. Finally, the text highlights the main contributions and lessons that can be drawn from these studies for accessibility in society at large and specifically in museumsKeywords: People with disabilities; accessibility and inclusion; disability studies; STS studies; accessibility in museums